(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study is to find out the frequency of musculoskeletal disorders among dentists working in Karachi and to establish factors associated with these disorders. Study Design: Cross-sectional descriptive and analytical study Place and Duration of Study: This study was conducted at Jinnah Medical and Dental College, Karachi from June 2014 to August 2014. The data was collected from three dental colleges of Karachi. Material and Methods: The study was conducted at Jinnah Medical and Dental College. The study included 222 dentists working in different faculty positions from house officers to professors. The data was collected to find out the frequency of musculoskeletal disorders among dentists working in five different dental institutions of Karachi. A 22-item questionnaire was used to collect the data. The questionnaire was validated among a group of five dentists before using it for final survey. The questionnaire consisted of number of questions about age, gender, number of years in profession, pain in the back and neck, working hours per day, number of patients treated per day, any break taken between patients or not, working with assistant or not, working positions used, and medicines taken due to musculoskeletal pain. The data was stored in excel worksheet and was analyzed using SPSS. Results: 222 dentists from five dental institutions of Karachi participated in the study. The study sample comprised of 90 males (40.5%) and 132 females (59.5%). The study highlighted that dentist who are involved in clinical practice are more prone to musculoskeletal problems accounting for about 79%. Amongst these 52.8% having backache, while 43.9% of the dentists having pain in the neck. The factors that were found to be significantly associated with musculoskeletal pain included; Dentists working without assistance experience more musculoskeletal problem approximately 47.6%. Dentist working more than 7 hours a day experienced more neck pain 40%. Conclusion: In the light of this study it is apparent that musculoskeletal disorders are very common amongst the dentist working in Karachi. It is seen more in those who are working for long hours and those working without trained assistants. Breaks between patients and reducing the number of working hours as well as trained dental assistance can reduce the incidence of these disorders.